2020
DOI: 10.1038/s41427-019-0163-5
|View full text |Cite
|
Sign up to set email alerts
|

Benzodithiophenedione-based polymers: recent advances in organic photovoltaics

Abstract: Over the past 20 years, significant progress has been made in organic photovoltaics (OPVs) due to its advantages of being cost-effective, being lightweight, and having flexible manufacturability. The optical-active layer of OPVs consists of a p-type polymer as the donor and an n-type small molecule as the acceptor. An efficient design strategy of a polymer donor is based on an alternating electron-donating unit (D) and an electron-accepting unit (A). Among numerous electron-accepting units, an emerging annelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 83 publications
0
74
0
Order By: Relevance
“…6, b41-43). 116 Fig. 6, b42) which achieved a PCE above 16% when paired with Y6 in a LbL OPV device.…”
Section: Ambipolar Small Moleculesmentioning
confidence: 96%
“…6, b41-43). 116 Fig. 6, b42) which achieved a PCE above 16% when paired with Y6 in a LbL OPV device.…”
Section: Ambipolar Small Moleculesmentioning
confidence: 96%
“…with planar backbone, the timescale as well as energetics of planarization will be modified and the absorbed energy can be utilized completely for carrier generation at higher V oc . Indeed recent studies have found reduced voltage loss and increment in PCE by choosing planar backbone organic semiconductors [19,20]. In-detail studies on correlating backbone planarity with carrier relaxation and photovoltaic performance will help to minimize loss channels in OPVs.…”
Section: Planarity Of Semiconductor Backbonementioning
confidence: 99%
“…Bulk heterojunction (BHJ) organic solar cells (OSCs) have been in favorable development in recent years, on account of their adjustable structure, flexibility, low cost, and more. [ 1–6 ] The joint advantages result in power conversion efficiencies (PCEs) of the state‐of‐the‐art photovoltaic devices over 17%. [ 7–12 ] The development of p‐type polymer donors plays a crucial role in the improvement of the photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%